2021
DOI: 10.1136/bmjdrc-2020-001909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tap dance on plantar pressure, postural stability and lower body function in older patients at risk of diabetic foot: a randomized controlled trial

Abstract: IntroductionTo examine the effects of tap dance (TD) on dynamic plantar pressure, static postural stability, ankle range of motion (ROM), and lower extremity functional strength in patients at risk of diabetic foot (DF).Research design and methodsA randomised, single-blinded, two-arm prospective study of 40 patients at risk of DF was conducted. The intervention group (n=20) received 16 weeks of TD training (60 min/session×3 sessions/week). The control group attended four educational workshops (1 hour/session×1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…The authors have shown that the use of dancing significantly improves cognitive functions and memory in people with Parkinson's disease. The works [39,40] also show a significant positive effect of dancing on the functional state of people with diseases of the cardiovascular system and metabolic disorders, in particular, those with diabetes. In patients with impaired cardiovascular activity, a significant decrease in blood pressure was noted [39].…”
Section: The Impact Of Dancing On the Health Of People Of Different Agesmentioning
confidence: 94%
See 2 more Smart Citations
“…The authors have shown that the use of dancing significantly improves cognitive functions and memory in people with Parkinson's disease. The works [39,40] also show a significant positive effect of dancing on the functional state of people with diseases of the cardiovascular system and metabolic disorders, in particular, those with diabetes. In patients with impaired cardiovascular activity, a significant decrease in blood pressure was noted [39].…”
Section: The Impact Of Dancing On the Health Of People Of Different Agesmentioning
confidence: 94%
“…Many studies are devoted to the therapeutic effect of dancing [31][32][33][34][35][36][37][38][39][40]. Ding et al [31] found a positive and significant effect of dance-based mental motor activity on the quality of life of patients recovering from COVID-19.…”
Section: The Impact Of Dancing On the Health Of People Of Different Agesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients are encouraged to take care of themselves and have their feet checked promptly 37 . Recently, a 16‐week tap dance training program had been shown to significantly improve ankle mobility, lower extremity functional strength, and static postural stability, but this approach was not suitable for patients with severe foot or joint deformities and weakness 44 …”
Section: Physical Therapy Of Dfumentioning
confidence: 99%
“…A feasibility test has indicated that the MTD program is a safe and feasible exercise and can be applied to older adults’ daily life. In addition, a recent study found that a 16 week course of the MTD can reduce the plantar pressure of diabetic patients who are at risk of diabetic foot [ 22 ]. However, the effects of the MTD on ankle function and postural control among healthy older adults remained unknown.…”
Section: Introductionmentioning
confidence: 99%